Путнамның есептеу ақыл гипотезасындағы күмәнді машиналардың автономиясы - Taye Oyelakin, Richard (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2020)
What appears as the main issue of debate between Putnam’s computational hypothesis and Searle’s Chinese room experiment is whether or not machine state is sufficient to account for the nature of human mental state. Putnam argues that the nature of machine states is synonymous to the nature of the mental states. For him, it follows that an understanding of the nature of Machine states is adequate to understanding the nature of the mental states. Searle’s challenge against Putnam’s computational hypothesis is anchored upon the popular Chinese Room Experiment. The experiment shows that it is possible to satisfy Putnam’s requirements for having a particular mental state without actually having the mental states in question, although Boden to the contrary. However, the debate is built upon an implied autonomy of machine state. That is, it is assumed that machine state has an independent existence from the mental state. Correspondingly, it is argued that for machine state to be used as an analogy in understanding the nature of mental state, it must be autonomous to mental state. The question which is being engaged in this paper is whether machine state is actually autonomous. For instance, how much can we understand by using the nature of the (mechanical) state of a wrist watch to study the nature of the mental state of the watch maker? The paper maintains that this autonomy of machine states from mental state is questionable. This is because, (1) There is yet no self-created/programmed computer machine, (2) Machine state is created or designed by human mental states and, (3) Only the nature of an autonomous entity could sufficiently be used to study the nature of another autonomous entity. The paper further argues that if an extreme position of the computational functionalism is maintained, then it raises more challenging questions and leads to more complicated problems. The paper, therefore, concludes that the view that intends to use the nature of machine state to study the nature of mental state is circular and the view that equates machine state with mental state is trivial. Key words: Chinese room, Computational Hypothesis, autonomy, Symbols and Codes, Computer machine, Machine table.